An Adhesive‐Integrated Stretchable Silver‐Silver Chloride Electrode Array for Unobtrusive Monitoring of Gastric Neuromuscular Activity. Issue 5 (8th April 2021) - Kurniawan, Jonas F.; Tjhia, Boris; Wu, Vincent M.; Shin, Andrew; Sit, Nathan L. J.; Pham, Timothy; Nguyen, Andrew; Li, Carleen; Kumar, Rajan; Aguilar‐Rivera, Marcelo; Lerman, Imanuel; Kunkel, David C.; et al.
Abstract: Here, an unobtrusive, adhesive‐integrated electrode array for continuous monitoring of stomach electric activity is introduced. This patient‐friendly, disposable peel‐and‐stick adhesive device represents an important advancement over existing arrays that require placement of each electrode individually and are thus also labor intensive and are in general more rigid and cumbersome. In comparison to other silver–silver chloride electrodes, this skin conformal array does not require gel and thus can withstand low impedance over the duration of long recordings. Interfacing these electrodes with miniaturized electronic recording and wireless telemetry systems has the potential to enable scalable population health opportunities to perform objective gastrointestinal assessment and optimization of treatment regimens. Abstract : This article presents a novel method for an unobtrusive continuous monitoring of gastric myoelectric activity. The authors utilize a patient‐friendly adhesive‐integrated peel‐and‐stick electrode array. Silver–silver chloride flexible electrodes enable a gel‐less application which can withstand duration of long recordings. Applications of this work have potential to improve gastrointestinal (GI) assessment and optimization of treatment regimens for patients with GI disorders.